2019
DOI: 10.1039/c9ra03970h
|View full text |Cite
|
Sign up to set email alerts
|

Inverted vortex fluidic exfoliation and scrolling of hexagonal-boron nitride

Abstract: Exfoliation or scrolling of hexagonal boron nitride (h-BN) occurs in a vortex fluidic device (VFD) operating under continuous flow, with a tilt angle of À45 relative to the horizontal position. This new VFD processing strategy is effective in avoiding the build-up of material that occurs when the device is operated using the conventional tilt angle of +45 , where the h-BN precursor and scrolls are centrifugally held against the wall of the tube. At a tilt angle of À45 the downward flow aided by gravity facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…7: 192255 electronic supplementary material, figure S4. We note that −45°tilt angle was effective in exfoliating h-BN in water [22]. Varying the different operating parameters of the VFD led to determining the optimal conditions for the exfoliation of MXene and the highest yield of material exiting (collected) the tube under continuous flow.…”
Section: Resultsmentioning
confidence: 98%
“…7: 192255 electronic supplementary material, figure S4. We note that −45°tilt angle was effective in exfoliating h-BN in water [22]. Varying the different operating parameters of the VFD led to determining the optimal conditions for the exfoliation of MXene and the highest yield of material exiting (collected) the tube under continuous flow.…”
Section: Resultsmentioning
confidence: 98%
“…The dynamic thin film in VFD is also effective in exfoliating other 2D materials including graphene and h ‐BN, with and without scrolling . In the present study, treating MXene with aqueous H 2 O 2 prior to VFD processing (batch processing) reduced the thickness of the MXene starting material from 10 μm to a few hundred nanometres, presumably driven by surface oxidation along dislocations in the material, Figure S5(d‐f).…”
Section: Resultsmentioning
confidence: 99%
“…[32] This is a proven approach for then translating any reaction into a continuous flow process, which is the other mode of operation of the VFD, Figure 1. [33] The VFD is a versatile thin film device effective for a growing number of applications, including in situ decorating h-BN with magnetite nanoparticles, [34] fabricating carbon dots from multi-walled carbon nanotubes, [35] chemo selective hydrogenation using cellulose impregnated with Pd NPs lining the VFD tube, [36] organic synthesis, [37][38] probing the structure of self-organised systems, [39][40] exfoliation and scrolling of h-BN and graphite, [41][42][43] slicing CNTs, [44][45] to mention a few. [41,[46][47][48][49][50][51][52][53][54] The VFD typically houses a borosilicate glass tube (O.D.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported the preparation of silica hydrogel using a VFD without the need for auxiliary reagents (solvent, acid, or base), promoting a new route for green chemistry. It was reported that the condensation of VFD- The VFD is a relatively low-cost research platform assisting efficient micromixing of chemicals and reactions, material synthesis, and both top-down and bottom-up strategies for the manufacture of nanoscale materials with complex structures, suggesting a range of benefits over conventional methods [63][64][65]. We successfully utilized a VFD for one-step fabrication of several physically and ionically crosslinked hydrogels with simultaneous control over their properties and surface morphology [66].…”
Section: Bulk Hydrogelsmentioning
confidence: 99%